2012
DOI: 10.1007/s00284-012-0269-2
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis Endospores at High Purity and Recovery Yields: Optimization of Growth Conditions and Purification Method

Abstract: Bacillus subtilis endospores have applications in different fields including their use as probiotics and antigen delivery vectors. Such specialized applications frequently require highly purified spore preparations. Nonetheless, quantitative data regarding both yields and purity of B. subtilis endospores after application of different growth conditions and purification methods are scarce or poorly reported. In the present study, we conducted several quantitative and qualitative analyses of growth conditions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 12 publications
1
27
1
Order By: Relevance
“…These values do not surpass the spore cell density reached by Chen et al [9], who reported a concentration of 1.52 9 10 10 CFU/mL for the B. subtilis WHK-Z12 strain, but to our knowledge, the sporulation efficiency reached in this work (93.5 ± 4.0 %) is the highest reported to date for B. subtilis strains that are in the range of 30-80 % [11,12,14].…”
Section: Resultscontrasting
confidence: 49%
See 1 more Smart Citation
“…These values do not surpass the spore cell density reached by Chen et al [9], who reported a concentration of 1.52 9 10 10 CFU/mL for the B. subtilis WHK-Z12 strain, but to our knowledge, the sporulation efficiency reached in this work (93.5 ± 4.0 %) is the highest reported to date for B. subtilis strains that are in the range of 30-80 % [11,12,14].…”
Section: Resultscontrasting
confidence: 49%
“…Under ideal conditions, typical cell densities and sporulation efficiencies for B. subtilis will be in the range of 1.00 9 10 8 -1.52 9 10 10 CFU/mL [9][10][11][12] and Electronic supplementary material The online version of this article (doi:10.1007/s00449-015-1428-1) contains supplementary material, which is available to authorized users. 30-80 %, respectively using serial dilution and plate count methods [11][12][13][14]. Other studies have reported higher sporulation efficiencies or higher spore cell densities for other Bacillus species different from B. subtilis [3,6,15,16], but to our knowledge obtaining high values of both variables has not been reported yet.…”
Section: Introductionmentioning
confidence: 98%
“…B. anthracis spores were prepared as described (Tavares et al ., ). Briefly, cells from sporulating cultures (50 ml) after 24 h of growth in DSM were harvested by centrifugation at 4°C for 10 min at 3,630 × g .…”
Section: Methodsmentioning
confidence: 97%
“…B. anthracis spores were prepared as described (Tavares et al, 2013). Briefly, cells from sporulating cultures (50 ml) after 24 h of growth in DSM were harvested by centrifugation at 48C for 10 min at 3,630 3 g. The bacterial pellets were washed once with 0.5 volume of distilled water and suspended in 10 ml of 10 mM Tris-HCl (pH 7.2) containing 50 lg/ml of lysozyme (Sigma-Aldrich).…”
Section: Sporulation Efficiency and Spore Preparationmentioning
confidence: 99%
“…B. subtilis WW02 is a widely used strain, which is a derivative from B. subtilis 1012, a reference laboratory strain with a sequenced genome and known physiological features [18], [19]. Spores were prepared from this strain, as previously described [20]. Briefly, sporulation of B. subtilis was induced following cultivation in F medium for 72 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%